Grit, motivational belief, self-regulated learning (SRL), and academic achievement of civil engineering students. (4th July 2022) - Martin, Hector; Craigwell, Renaldo; Ramjarrie, Karrisa
ABSTRACT: The influence of grit on engineering student's achievement has been understudied. The association between grit, self-regulated learning (SRL), and academic achievement in civil engineering students was investigated using correlation and regression analysis. One hundred and one civil engineering students from various nationalities completed a self-report questionnaire that contained the Grit 12-item scale and the forty-four questions on motivational beliefs and self-regulated learning practices (MSLQ). Four of the five SRL variables were predicted by perseverance of effort: intrinsic value, self-efficacy, cognitive strategy use, and self-regulation. Initially, perseverance of effort predicted the current grade point average (GPA), but it was no longer a predictor after including SRL indicators. Consistency of interest was a predictor of cognitive strategy usage, but it did not affect students' academic achievement. GPAs were also predicted by student self-efficacy and age. The connection between academic accomplishment and grit is mediated by SRL engagement. Students' perceived competency and confidence in completing their degree were shown to be major determinants of their GPA. Furthermore, motivational beliefs had a greater effect on students' GPAs than grit did. In the majority of the study's constructs, female students outperformed males. GPAs were higher among younger students than among their older peers.